THU0234 Clinical Experience and Decision Making in Relation To The Use of Biologics in Adult JIA. (15th July 2016) - Smith, N.; Rapley, T.; McErlane, F.; Kearsley-Fleet, L.; Hyrich, K.L.; Foster, H.E.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) is the most common chronic inflammatory musculoskeletal disease of childhood in the UK. More than 30% of patients will continue to have active disease as adults, with some requiring a biologic for the first time after the age of 18 years. Prior to December 2015, there was no national UK approval for the use of biologics in this older population, albeit they were used in adults with JIA (British Society for Rheumatology Biologics Register BSRBR Data). Objectives: This mixed methods study aimed to explore the clinical experience and decision-making of health care professionals in relation to the use of biologics in adults with JIA. Methods: An online survey of 205 healthcare professionals working in UK hospitals who have recruited adults with JIA to BSRBR-RA (response rate: 81 (39%) including rheumatology consultants (49), rheumatology specialist nurses (29), research nurses (2) and staff associates (1)), ascertained their experience in relation to four distinct areas: (1) Education, Training and Practice; (2) Factors Suggesting a Diagnosis of JIA, (3) Use and Choice of Biologics; and (4) Treatment Challenges. The survey data were analysed using descriptive statistics and free-text comments using qualitative techniques. This study had ethical approval with informed consent from all participants. Results: Most (95%) survey participants currently treat adults with JIA and many (63%) also treat children. Most had not received any education or training in the specific management of adults with JIA (65%) although 56% had received some training in paediatrics (described as formal training programmes, attendance at meetings; in practice learning and colleague support). Many stated further need for training in JIA in adults (52%) and children (58%). Participants reported using all currently approved biologics for either JIA in children or rheumatoid arthritis; etanercept, adalimumab and tocilizumab being the most common. Factors influencing choice included: National guidelines and funding; JIA disease-associated factors; patient previous treatment; previous experience of clinician; and patient choice. The challenges encountered in treating adults with JIA included: access to biologic therapy; JIA awareness and knowledge; access to support from colleagues and MDT; problems associated with transitional care services; and patient expectations. Potential improvements to aid the diagnosis and management of adults with JIA were offered and these included: Introduction of national guidelines; further education/training and support; and introduction or improvement of transition service links. Conclusions: Improved access to education, training and treatment guidelines in JIA is likely to improve clinical experience and decision-making in relation to the management of adults with JIA. Future qualitative work will explore this further. Disclosure of Interest: None declared